Comparison of 99mTc-DMSA Renal Scan and Power Doppler Ultrasonography for the Detection of Acute Pyelonephritis and Vesicoureteral Reflux - Hee Jung Bae; Yong-Hoon Park; Jae Ho Cho; Kyung Mi Jang (Korean Society of Pediatric Nephrology, 2018)
Purpose Urinary tract infection (UTI) is one of the common infectious diseases in children. Several imaging modalities can be used to confirm the presence of acute pyelonephritis (APN). Among them the 99mTcdimercaptosuccinic acid renal scan (DMSA scan) is used as a gold standard for diagnosis. Ultrasonography technology is evolving. Therefore, in this study, we investigated the sensitivity and specificity of Power Doppler ultrasonography (PDU) compared to the results from the previous study. Methods There were 260 patients included in this study, aged between 1 and 12 months old. The patients were admitted to the Yeungnam University Medical Center between January 2008 and December 2015. All patients underwent both DMSA scan and PDU within 5days of admission. Voiding cystourethrography (VCUG) was performed in 195 patients with abnormal DMSA scan or PDU. Results The diagnostic sensitivity of APN using PDU was 45.5% and specificity was 85.5% in 260 patients following detection of a defect on DMSA scan that was defined as APN. The diagnostic sensitivity and specificity of PDU for VUR were 65.5% and 60.1%, respectively. The diagnostic sensitivity and specificity of DMSA scan for VUR were 95.7% and 14.1%, respectively. Conclusion PDU has a high specificity but low sensitivity, so there are limitations in using it to replace a DMSA scan for the diagnosis of APN in children. DMSA scan and PDU have different sensitivity and specificity in diagnosis of VUR, respectively. Therefore, we suggest that the sensitivity and specificity of each test can be helpful in diagnosing APN and VUR when used in conjunction.